Concept of dependent joints in functional reconfigurable robots. Issue 3 (6th July 2015) - Mekid, Samir; Shang, M.
Abstract : Purpose: – The purpose of this paper is to discuss an example of modelling with experiments of robot prototype with dependent joint concept, including a full description of related functionalities. Reduction in active degrees of freedom in a machine can lead to improved accuracy, improved reliability and lower cost. The reconfiguration of machines and systems is a key technology for future responsive manufacturing systems. The concept of dependent joints helps to implement much specified sub-workspaces depending on functional needs in the machine. Design/methodology/approach: – This is inherently made possible using smart mechanical concepts having embedded sensors and reconfigurable control systems. This paper introduces structural reconfiguration systems and discusses a sample approach to functional reconfiguration. Findings: – A successful manipulator design with extended features when considering reduction in active degrees of freedom in a machine would lead to specific sub-workspace with improved accuracy, improved reliability and lower cost. Research limitations/implications: – Reduction in active degrees of freedom in a machine can lead not only towards a dedicated functional workspace but also towards improved accuracy, improved reliability and lower cost. Originality/value: – This paper is of value to engineers and researchers developing robotic manipulators for use in various aspects of industry.